An ensemble approach to quantify global mean sea-level rise over the 20th century from tide gauge reconstructions - Palmer, M D; Domingues, C M; Slangen, A B A; Boeira Dias, F (Environmental research letters, 2021)
We present an ensemble approach to quantify historical global mean sea-level (GMSL) rise based on tide gauge reconstructions. This approach combines the maximum internal uncertainty across the ensemble with an estimate of structural uncertainty to provide a conservative estimate of the total uncertainty. Comparisons of GMSL rise over the 20th century based on deltas and linear trends (and their respective uncertainties) are consistent with past Intergovernmental Panel on Climate Change assessments and show good agreement with satellite altimeter timeseries. Sensitivity tests show that our estimates of GMSL rise are robust to the choice of reference period and central estimate timeseries. The methods proposed in this study are generic and could be easily applied to other global or regional climate change indicators.